Relationship Between Multiple Intelligences and Student's Mathematical Connection Ability - Agustina Agustina; Ervin Azhar (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2021)
When learning in school when students are given a problem, of course each student gives a different answer, this shows that each student has a different intelligence in solving this problem. We call these different intelligences as multiple intelligence. Each question must of course be solved with intelligence, especially in learning mathematics, students often find it difficult to solve problems in the form of stories that are related to everyday life. Connecting problems in mathematics with everyday life is one indicator of the ability to connect mathematics. Indirectly, students who have difficulty solving math problems associated with everyday life cause the students to have low mathematical connection skills. This study aims to see whether there is a relationship between multiple intelligence and students' mathematical connection abilities. The research method used is an associative quantitative research method with the spearman rank correlation test. The instruments in this study were a statement questionnaire to measure multiple intelligence and a test question instrument to measure students' mathematical connection abilities. This study involved 97 samples from class VIII students at SMP Puspanegara Citeureup. The results of the analysis in this study indicate that there is a significant relationship between multiple intelligence and the Mathematical Connection Ability of grade VIII students at SMP Puspanegara Citeureup. This is evidenced by the coefficient of the relationship between multiple intelligence and the students' mathematical connection ability of 0.720. Based on the interpretation of values, it shows that there is a strong relationship between multiple intelligence and the ability of mathematical connections. Keywords: multiple intelligence, mathematics, connections.